Continuous synthesis of star polymers with RAFT polymerization in cascade microreactor systems. (22nd April 2021) - Xiang, Liang; Qiu, Min; Shang, Minjing; Su, Yuanhai
Abstract: With the RAFT arm-first method, butyl acrylate and 4-acryloylmorpholine were used as monomers to form linear arms, which subsequently reacted with the cross-linker 1, 6-hexanediol diacrylate to form star-shaped macromolecules in cascade microreactor systems. After studying polymerization kinetics in each step, homoarm and miktoarm star products with various arm compositions were steadily prepared by optimizing the reaction flowsheet and adjusting the reactant formula. Such continuous-flow processing avoided tedious intermediate purification procedures and prepared polymer products with considerable star yield (>70%), molecular weights ( M w, LS > 100 kg/mol) and arm numbers (>30). Multiple emulsions (including two types, i.e., oil-in-water and water-in-oil) were formed utilizing star products with different amphiphilic architectures as emulsifiers. This study demonstrated that in this continuous-flow mode, through regulating the residence time and flow rate ratio in each step, the arm and core structures of star polymers were tailored to possess remarkable functional applications. Graphical abstract: Image 1 Highlights: A cascade microreactor platform for the synthesis of star polymers was developed. Continuous-flow processing integrated the arm and star formation steps without intermediate purification. Parameters affecting star structures were optimized and kinetics was discussed. Star polymers with varied compositions and amphiphilic properties were tailored. Applications as emulsifiers were related to the arms and cores of star polymers.